2006
DOI: 10.1109/tmag.2006.879966
|View full text |Cite
|
Sign up to set email alerts
|

Conductive Microbead Array Detection Based on Eddy-Current Testing Using SV-GMR Sensor and Helmholtz Coil Exciter

Abstract: This paper describes the detection of both single and array conductive microbead (PbSn) by using a spin-valve giant magnetoresistance (SV-GMR) as a sensor and the Helmholtz coil as an exciter based on eddy-current testing (ECT). Experiments were performed to detect a single and array conductive microbead, with three models. Each model consists of 4 4 microbeads but the microbead diameter and pitch were slightly different for each array. The microbead radius was 125 m and the pitch was 500 m. The ECT method was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…The numerical gradient technique is applied to ECT signals obtained from the detection of solder microbeads [47,48]. The results show that the numerical gradient is able to enhance the signal at the microbead as shown in Fig.…”
Section: Ball Grid Array Detectionmentioning
confidence: 99%
“…The numerical gradient technique is applied to ECT signals obtained from the detection of solder microbeads [47,48]. The results show that the numerical gradient is able to enhance the signal at the microbead as shown in Fig.…”
Section: Ball Grid Array Detectionmentioning
confidence: 99%
“…One of the most common applications of GMR is in magnetoelectronic devices such as magnetic field sensors [1], magnetoresistance random access memories, magnetoresistance transistors. GMR sensors have found applications in hard drives [2][3][4], position detection, nondestructive evaluations [5][6][7], and conductive microbead detection [8]. Applications in utilization of GMR chips whose surface is bound with biological tagged markers can be found in [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent year, the ECT has been successfully applied to detection of flaw on printed circuit board (PCB) 4) . In the previous work, we reported that the ECT probe had been applied to detect the conductive microbead of both single and array 5) .…”
Section: Introductionmentioning
confidence: 99%